Determinants of Parental Rejection in Implementing Immunization in Children Post Covid-19 - Henni Fitriani; Fachmi Ichwansyah; Asnawi Abdullah; Marthoenis Marthoenis; Hafnidar A Rani (Indonesian Journal of Global Health Research, 2025)
Complete basic immunization coverage in Pidie Regency, Aceh Province, is still very low after the COVID-19 pandemic, which has increased the risk of diseases that can be prevented. This study analyzes the determinants of parental refusal to implement complete basic immunization in children aged 0–2 years. The study used a mixed methods approach with a cross-sectional design for quantitative and in-depth interviews for qualitative. A quantitative sample of 270 respondents was selected using the cluster random sampling method, while qualitative informants were selected using purposive sampling. The analysis showed that the number of children, attitudes, family support, health worker behavior, the role of community and religious leaders, and exposure to information was significantly related to immunization refusal (p <0.05). Qualitative findings revealed that the issue of halal-haram vaccines and the influence of local traditions were the main obstacles. The factors of the number of children (OR=3.47), attitudes (OR=0.19), family support (OR=0.16), and exposure to information (OR=0.24) were the dominant determinants.